Studies on the Indian Gharial Gavialis gangeticus (Gmelin) (Reptilia, Crocodilia) -I: Estimation of Body Length from Scute Length - Bustard, H. R.; Singh, L. A. K. (Indian Forester, 1977)
A basking gharial Gavialis gangeticus (Gmelin), often leaven at the basking site, impressions of the single row tail scutes of the ventral region. The growth of these scutes (SC) bear a linear relationship to the growth of the total body length (TBL). TBL=53.658+62.733 (SC). This statistic, with fair degrees of accuracy, has been proved with four wild gharials and three captive gharials ranging from 1.4 to 5.4 m in total length. It is presumed that a similar relationship exists for other crocodilian species too. This method of size estimation from the tail scute spoor can be safely used for census and movement studies.